Karakter Pertumbuhan dan Produksi Kedelai Edamame (Glycine max (L.) Merril) pada Perlakuan Jarak Tanam dan Konsentrasi Paclobutrazol : Growth and Production Attributes of Edamame Soybean (Glycine max (L.) Merril) in Plant Distance and Paclobutrazol Concentration Treatments - Lala Fitriansyah Gani; Ahmad Rifqi Fauzi (Politeknik Pertanian Bogor, 2023)
Edamame soybeans have a higher productivity potential than ordinary soybeans. Edamame can be an alternative to meet the national demand for soybeans which have a high level of consumption. This research aims to determine the effect of spacing and paclobutrazol on the growth and productivity of edamame soybeans. The study was conducted in Sukarame Village, Caringin, Garut Regency and the Laboratory of Agroecotechnology Study Program, Universitas Trilogi from March to June 2022. The study used a factorial Randomized Complete Block Design (RCBD) with three replications. The first factor is the spacing consisting of J1 = 30 cm x 25 cm, J2 = 30 cm x 20 cm, J3 = 30 cm x 15 cm, and J4 = 30 cm x 10 cm. The second factor was the paclobutrazol concentration consisting of P0 = without paclobutrazol (control), P1 = 100 ppm. The results was no interaction between the spacing treatment and the paclobutrazol concentration. Based on the first factor, the results were significantly different on the plant height in the third week of treatment spacing of 30 cm x 10 cm and weight of 100 seeds from spacing of 30 cm x 15 cm). The paclobutrazol factor had significantly different results in plant height and number of pods with the best results without paclobutrazol treatment.